Further Advanced Chemistry - Earl, B. (Bryan), 1960-; Wilford, L. D. R. (London : John Murray, 2001)
This text is written specifically to cover the new A Level specifications for chemistry. The book includes chapters on: kinetics, thermodynamics, aldehydes and ketones, aromatic chemistry and polymers.
Includes index.
Keywords: Chemistry; Chemistry -- Examinations -- Study guides; Popular Science and Mathematics